2014
DOI: 10.1158/1055-9965.epi-13-1329
|View full text |Cite
|
Sign up to set email alerts
|

PLCE1 mRNA and Protein Expression and Survival of Patients with Esophageal Squamous Cell Carcinoma and Gastric Adenocarcinoma

Abstract: Background Germline genetic variants in PLCE1 (10q23) have demonstrated consistent associations with risk of esophageal squamous cell carcinoma (ESCC) and gastric cancer among Chinese. We evaluated PLCE1 mRNA and protein expression in paired tumor-normal tissues, and their relationship with survival. Methods PLCE1 mRNA was profiled using three probes in the Affymetrix GeneChip U133 for paired tumor-normal tissues of ESCC (n=132), gastric cardia adenocarcinoma (GCA, n=62) and gastric noncardia adenocarcinoma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 36 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…With the rapid development of highthroughput detection techniques, gene expression data are accumulating rapidly in public repositories and a massive amount of differentially expressed genes (DEGs) between GC and normal tissue has been identified in several studies [5][6][7][8][9] . Many DEGs have been validated as oncogenes or tumor suppressors, which effect different malignant phenotypes of GC including proliferation, angiogenesis, metastasis, and chemoresistance via activating or inactivating multiple downstream signaling pathways [5][6][7][8][9] . But owing to different sample resources, experimental techniques, and bioinformatics algorithms, the results among these studies are greatly divergent, and there is still no widely accepted factor dominating the malignant transformation and progression of GC.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of highthroughput detection techniques, gene expression data are accumulating rapidly in public repositories and a massive amount of differentially expressed genes (DEGs) between GC and normal tissue has been identified in several studies [5][6][7][8][9] . Many DEGs have been validated as oncogenes or tumor suppressors, which effect different malignant phenotypes of GC including proliferation, angiogenesis, metastasis, and chemoresistance via activating or inactivating multiple downstream signaling pathways [5][6][7][8][9] . But owing to different sample resources, experimental techniques, and bioinformatics algorithms, the results among these studies are greatly divergent, and there is still no widely accepted factor dominating the malignant transformation and progression of GC.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains controversial whether PLCE1 acts as an oncogene or a tumor suppressor in ESCC development and progression. Hu et al (10) and Li et al (24) reported decreased mRNA in ESCC tumors compared with that in the adjacent normal esophagus, but no difference in protein expression. By contrast, ESCC tissues exhibited a higher PLCE1 protein expression compared with normal tissues in other studies (3,23,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, one study reported that high PLCE1 protein expression in ESCC was associated with poor survival (23), while increased tumor/normal-fold change of mRNA and protein expression in ESCC was associated with improved survival in another study (24). To the best of our knowledge, the present study is the first to evaluate the association between the rs2274223 SNP and survival of ESCC patients of Han nationality, and found no correlation, which is similar to the results in the northern Indian population (7).The PLCE1 rs2274223 SNP, a non-synonymous SNP causing an amino acid change from His to Arg in the 26th exon, is located at the calcium-binding domain, indicating its crucial functional significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PLCE1 is thought to act as an oncogene in bladder cancer [42, 43], non-small cell lung cancer [44], skin cancer [45], and head and neck cancer [46]. Upregulation of PLCE1 mRNA level is associated with longer survival in gastric cardia adenocarcinoma (GCA) and ESCC, while the transcript is downregulated in GCA and ESCC tumor tissue [47], which was confirmed by another study of ESCC patients [30]. However, higher PLCE1 expression was observed in Chinese Kazakh ESCC patients and ESCC tumor cell lines [48].…”
Section: Discussionmentioning
confidence: 99%